Simultaneous strength-ductility enhancement in as-cast Ti6Al4V alloy by trace Ce. (March 2022) - Li, K.M.; Liu, Y.J.; Liu, X.C.; Wu, X.; Zhou, S.F.; Zhang, L.C.; Li, W.; Zhang, W.C.
Graphical abstract: Highlights: The impurity elements in as-cast Ti6Al4V alloy can be adsorbed by Ce element. The grain size of as-cast Ti6Al4V alloy can be refined by adding trace Ce element. The strength and elongation of as-cast Ti6Al4V alloy are improved simultaneously due to pinning effect of Ce-rich precipitates. Abstract: Impurity elements always play a major role in hindering mechanical property improvement in Ti6Al4V, and specifically most of them e.g. O, P, Cl, and S dissolved in the matrix deteriorate the mechanical properties of Ti6Al4V. This work presents a strategy of enhancing the mechanical performance of as-cast Ti6Al4V alloy by adding a small amount of rare earth (i.e. 0.1 wt% Ce), where deleterious elements could be absorbed from the crystalline lattice during solidification process, forming uniformly distributed Ce-rich oxides or precipitates with ∼200 nm in size. The Ce-rich precipitates in turn refine the beta phase lamellae by introducing more nucleation in the cast alloy, which further enhances the strength. As such, the cast Ti6Al4V with Ce addition exhibits a tensile strength of 957 ± 47 MPa and elongation of 12.3%, which exhibits a simultaneous strength-ductility enhancement compared with the Ti6Al4V counterpart (787 ± 65 MPa and 8.8%). In addition, the Ce-rich precipitates also pin dislocation motions, which effectively shields the stress concentration at the crack tip and deflects the crack propagation during fracture process.